CLASSIFICATION OF THE RUSSIAN FEDERATION GOVERNMENT DECISIONS AND THE STANDARDS CONTAINED THEREIN, APPLIED IN CRIMINAL PROCEDURAL ACTIVITIES - VALYULIN RUSLAN (Legal Bulletin)
The article presents a practical examination of Government Regulations of the Russian Federation as a source of criminal procedure law. The author argues that the prevailing formal-hierarchical approach fails to reflect the functional diversity of delegated legislation, because many regulations de facto create primary rules shaping criminal proceedings. The aim is to elaborate a multi-criteria classification ensuring accurate interpretation and uniform application of these acts. The methodological framework combines the functional approach with legal hermeneutics, allowing identification of the regulatory purpose of norms and interpretation of their content within the context of the Code of Criminal Procedure. A five-criterion typology is substantiated: (1) mode of integration into the Code; (2) procedural stage of operation; (3) regulatory method (restrictions versus guarantees); (4) degree of behavioural regulation (autonomous versus specifying norms); (5) degree of certainty and influence on decision-making. The model was tested on fifteen regulations adopted between 2006 and 2024, including Nos. 1240, 134 and 1589, and compared with foreign theories of delegated rule-making. The proposed classification enhances legal certainty, reduces risks of misclassifying normative force and improves investigative and judicial practice. Theoretical contribution lies in refining the conceptual apparatus of source-of-law doctrine and revealing the heuristic value of a functional-hermeneutic synthesis for procedural scholarship. Study limitations relate to its focus on federal regulations. Future research should apply the typology to acts of other executive bodies and compare the Russian model with Continental and common-law systems across diverse regulatory levels. Findings may guide lawmakers, courts and investigators in calibrating rule-making practices.